2014
DOI: 10.1038/tp.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of loci from the International Genomics of Alzheimer’s Disease Project identifies TRIP4 as a novel susceptibility gene

Abstract: To follow-up loci discovered by the International Genomics of Alzheimer's Disease Project, we attempted independent replication of 19 single nucleotide polymorphisms (SNPs) in a large Spanish sample (Fundació ACE data set; 1808 patients and 2564 controls). Our results corroborate association with four SNPs located in the genes INPP5D, MEF2C, ZCWPW1 and FERMT2, respectively. Of these, ZCWPW1 was the only SNP to withstand correction for multiple testing (P=0.000655). Furthermore, we identify TRIP4 (rs74615166) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 19 publications
(23 reference statements)
0
63
0
1
Order By: Relevance
“…Among these, SORL1 had been identified in a GWAS of Japanese, Korean, and Caucasian AD cases and controls (the lattermost taken from the ADGC), however, as a well-established functional candidate, it had not been observed in a GWAS of European ancestry until the IGAP analyses, likely due to its low minor allele frequency (MAF) of ~0.04. Subsequent replication efforts have provided confirmation of the signal in ZCWPW1 (Ruiz et al, 2014) as well as evidence of association at TRIP4 . Multiple validation studies (studies examining associations among different ethnicities) in Southeast Asian populations have demonstrated associations at many of these loci: CLU (Komatsu et al, 2011; Liu et al, 2014; Yu et al, 2013), CR1 (Jin et al, 2012), PICALM (Chung et al, 2013; Liu et al, 2013; Miyashita et al, 2013), BIN1 (Liu et al, 2013; Miyashita et al, 2013), and the MS4A gene cluster (Deng et al, 2012; Tan et al, 2013).…”
Section: Genetics Of Alzheimer Disease: Late-onset Alzheimer Disease mentioning
confidence: 89%
“…Among these, SORL1 had been identified in a GWAS of Japanese, Korean, and Caucasian AD cases and controls (the lattermost taken from the ADGC), however, as a well-established functional candidate, it had not been observed in a GWAS of European ancestry until the IGAP analyses, likely due to its low minor allele frequency (MAF) of ~0.04. Subsequent replication efforts have provided confirmation of the signal in ZCWPW1 (Ruiz et al, 2014) as well as evidence of association at TRIP4 . Multiple validation studies (studies examining associations among different ethnicities) in Southeast Asian populations have demonstrated associations at many of these loci: CLU (Komatsu et al, 2011; Liu et al, 2014; Yu et al, 2013), CR1 (Jin et al, 2012), PICALM (Chung et al, 2013; Liu et al, 2013; Miyashita et al, 2013), BIN1 (Liu et al, 2013; Miyashita et al, 2013), and the MS4A gene cluster (Deng et al, 2012; Tan et al, 2013).…”
Section: Genetics Of Alzheimer Disease: Late-onset Alzheimer Disease mentioning
confidence: 89%
“…In addition, 2 novel loci, TP53INP1 (p = 1.4 × 10− 6 ) and IGHV1-67 (p = 7.9 × 10− 8 ), showed genome-wide association for disease [13] (table 1). More recently, TRIP4 (p = 9.74 × 10− 9 ) has been confirmed as an AD risk locus when single nucleotide polymorphism (SNP) data from the IGAP data set was combined with data from additional genotyping in an independent sample (Fundació ACE data set; 1,808 patients and 2,564 controls) [14] (table 1). Also of note is PLD3; gene burden analysis of PLD3 variants showed a significant association with disease, suggesting that multiple variants in the gene contribute to disease [15].…”
Section: Genetic Findingsmentioning
confidence: 99%
“…Through genome-wide association studies (GWASs), around 20 genetic loci had been discovered, which affect risk of LOAD (Lambert et al, 2013). Follow-up studies based on the GWAS have identified other potential candidate AD risk genes not previously identified, including the TRIP4, SPPL2A (Ruiz et al, 2014), and ABI3 genes (Sims et al, 2017). Next-generation sequencing has also enabled the identification of rare variants, one of the most consistent being the R47H variant in the TREM2 gene locus (Guerreiro et al, 2013; Jonsson et al, 2013) which affect the risk of AD previously not identified in GWAS (Giri et al, 2016; Lambert et al, 2013; Naj and Schellenberg, 2016).…”
Section: Introductionmentioning
confidence: 99%